La conciencia lingüística en el proceso de la lecto-escritura - Moreno Molina, Paola Alexandra (2021)
This research has been carried out with the purpose to use new methodologies in the teaching process of reading-writing, such as the development of linguistic conscience, since this study enables to overcome the flaws in the students, how also lets to keep motivated and creative and besides helps in the formation of critical, determined and reflective entities, making easy their development in society. The intention of this methodology is to maintain communicative situations, taking in account their cognitive development based in the mental processes of thinking, feeling, learning and retention. That is why strategies, besides innovative, have a special interest how the individual perceives, interprets, stores and retrieves information. In the future it will allow students to expand their opportunities to participate in important events in the whole world. It should be noted that readingwriting is the basis of quality teaching. Therefore, a greater emphasis must be maintained to achieve the expected results. This methodology was proposed by the Reading Schools of the Simon Bolivar Andean University who consider that it builds knowledge from the experience that the student therefore has the importance of developing linguistic awareness from early ages.